Impact of SNP array karyotyping on the diagnosis and the outcome of chronic myelomonocytic leukemia with low risk cytogenetic features or no metaphases. Issue 2 (9th December 2015) - Palomo, Laura; Xicoy, Blanca; Garcia, Olga; Mallo, Mar; Ademà, Vera; Cabezón, Marta; Arnan, Montse; Pomares, Helena; José Larrayoz, María; José Calasanz, María; Maciejewski, Jaroslaw P.; Huang, Dayong; et al.
Abstract : Chronic myelomonocytic leukemia (CMML) is a clonal hematopoietic disorder with heterogeneous clinical, morphological and genetic characteristics. Clonal cytogenetic abnormalities are found in 20–30% of patients with CMML. Patients with low risk cytogenetic features (normal karyotype and isolated loss of Y chromosome) account for ∼80% of CMML patients and often fall into the low risk categories of CMML prognostic scores. We hypothesized that single nucleotide polymorphism arrays (SNP‐A) karyotyping could detect cryptic chromosomal alterations with prognostic impact in these subgroup of patients. SNP‐A were performed at diagnosis in 128 CMML patients with low risk karyotypes or uninformative results for conventional G‐banding cytogenetics (CC). Copy number alterations (CNAs) and regions of copy number neutral loss of heterozygosity (CNN‐LOH) were detected in 67% of patients. Recurrent CNAs included gains in regions 8p12 and 21q22 as well as losses in 10q21.1 and 12p13.2. Interstitial CNN‐LOHs were recurrently detected in the following regions: 4q24–4q35, 7q32.1–7q36.3, and 11q13.3–11q25. Statistical analysis showed that some of the alterations detected by SNP‐A associated with the patients' outcome. A shortened overall survival (OS) and progression free survival (PFS) was observed in cases where the affected size of the genome (considering CNAs and CNN‐LOHs) was >11 Mb. In addition, presence of interstitial CNN‐LOH was predictive of poor OS. Presence of CNAs (≥1) associated with poorer OS and PFS in the patients with myeloproliferative CMML. Overall, SNP‐A analysis increased the diagnostic yield in patients with low risk cytogenetic features or uninformative CC and added prognostic value to this subset of patients. Am. J. Hematol. 91:185–192, 2016. © 2015 Wiley Periodicals, Inc.